Kandungan Protein, Lemak, Dan Karbohidrat Pada Biomassa Spirulina platensis Yang Kultivasi Pada Media Berbasis Kotoran Burung Puyuh - Shokimun Mega Samudera; Tatang Sopandi (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2020)
The components of providing nutritional media are a high cost in the cultivation of Spirulina platensis. It is necessary to search for media sources of nutrition in S.platensis cultivation to reduce production costs and increase income. This study aimed to evaluate the protein, fat and carbohydrate content of S. platensis biomass cultivated in quail manure media. The study was conducted from March to June 2020 using an experimental method with a completely randomized design (CRD) consisting of 4 treatments and 6 replications. The concentrations of quail manure used as a source of nutrition in this study consisted of 50, 100 and 150 g/L and Zarrouk's medium was used as a control or standard media. The results showed that the concentration of quail manure had a significant effect (P <0.05) on the protein, fat, and carbohydrate content of S platensis biomass. The optimum concentration for using quail dung as a cultivation medium for S.plantesis is 100 g/L. Keywords: Spirulina platensis, quail manure, protein, carbohydrates, fat